Bevacizumab as a mitigating factor for the impact of high systemic immune-inflammation index on chemorefractory in advanced epithelial ovarian cancer - Yan-Ping Fu; Hao Lin; Yu-Che Ou; Chen-Hsuan Wu; Hung-Chun Fu (BMC Cancer)
Abstract Background Predicting chemorefractory disease in advanced epithelial ovarian cancer (EOC) remains challenging. This study aimed to identify clinicopathological factors and hemogram data as predictive markers for chemorefractory EOC and to explore potential therapeutic approaches that may mitigate these unfavorable conditions. Methods We conducted a retrospective analysis of patients with advanced EOC treated with chemotherapy. Hemogram data and clinicopathological variables were collected. We employed logistic regression to assess factors associated with chemorefractory EOC and used the Kaplan–Meier method for survival analysis. Results Among the 191 patients analyzed, suboptimal surgery, lymphocyte count < 1440/mm3, systemic immune-inflammation index (SII) ≥ 2350, and lack of bevacizumab therapy were independently associated with chemorefractory EOC (OR 19.30, 95% CI 7.01—53.12; OR 9.07, 95% CI 2.76—29.82; OR 12.45, 95% CI 3.87—40.07; OR 6.61, 95% CI 2.01—21.78, respectively). Elevated SII was also identified as a risk factor for poor progression-free (PFS) and overall survival (OS). Specifically, patients with high SII who did not receive bevacizumab had a significantly higher probability of chemorefractory EOC and poorer survival outcomes compared to those who received bevacizumab. Conclusions Our findings suggest that hemogram parameters and clinicopathological factors such as suboptimal surgery, lymphocyte count, SII, and bevacizumab therapy status are predictive markers for chemorefractory disease in advanced EOC. Elevated SII emerged as a predictor for poorer PFS and OS outcomes, particularly in the absence of bevacizumab therapy.